The reality and obstacles to the use of public education teachers in Tabuk, Saudi Arabia, for open educational resources OER - Alhwaiti, Metib Habis Jazaa (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the reality and constraints of using general education teachers in Tabuk, Saudi Arabia for open educational resources OER, and to achieve the goals of the study, the researcher used the descriptive survey method, and the tool was a questionnaire distributed to the study sample of (369) teachers in Tabuk City schools In the year 1439-1440 AH. The results were: the overall instrument obtained an average (2.59 out of 5) with a (large) estimate in the following aspects; the reality of public education teachers using open educational resources (Shams platform) in their teaching practices obtained an average (2.65 out of 4) and the aspect of obstacles for the use of education teachers got the year of open resources (Shams platform) is on average (2.53 out of 4) and both are rated (large), The results of the study also revealed that there were statistically significant differences at (α≤ 0.05) between the responses of the sample about the reality of teachers of general education using open educational resources in their teaching practices and about obstacles to use; due to the following variables: (specialization; scientific - literary; and in favor of the scientific category, According to the variable: Training in the field of open educational resources in the axis of using open education resources for the benefit of those who got training, while there were no differences according to the variable in the axis of obstacles, and there were no statistically significant differences according to the rest of the variables (school stage, years of experience, qualification Scientific) Results were presented a number of recommendations and proposals to activate the use of open educational resources, and at the forefront of training for teachers.